Direct secondary flux oriented control of linear induction motor drive - Rathore A.K.; Mahendra S.N. (My University, 2025)
When driven by a field-oriented controller, also known as vector controller, induction machine behaves like a separately excited DC machine where flux and motion dynamics are controlled independently in order to achieve high performance from the IM drives. In this paper, the authors have investigated the performance of a linear induction motor drive driven by direct field oriented controller using a commercially available software package Matlab/Simulink.